2009
DOI: 10.1590/s0037-86822009000400001
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus and human T-lymphotropic virus coinfection: epidemiological, clinical, laboratory and histopathological features

Abstract: Twenty-four hepatitis C virus patients coinfected with human T-lymphotropic virus type 1 were compared with six coinfected with HTLV-2 and 55 with HCV alone, regarding clinical, epidemiological, laboratory and histopathological data. Fischer's discriminant analysis was applied to define functions capable of differentiating between the study groups (HCV, HCV/HTLV-1 and HCV/HTLV-2). The discriminant accuracy was evaluated by cross-validation. Alcohol consumption, use of intravenous drugs or inhaled cocaine and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…23 However, other groups have postulated that HTLV-1 infection can attenuate hepatic damage, as shown by lower serum levels of aminotransferases and lower degrees of liver fibrosis. 27,28 Similar results were observed in a study with triple HIV, HCV, and HTLV-1 co-infection, in which HTLV-1-infected patients presented better outcomes for HCVassociated liver fibrosis. 26 The present study was performed to provide new insights into the interactions between HCV and HTLV-1 infections through an evaluation of abnormalities in hepatic parameters and the neurological outcomes of HCV/HTLV-1 co-infection.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…23 However, other groups have postulated that HTLV-1 infection can attenuate hepatic damage, as shown by lower serum levels of aminotransferases and lower degrees of liver fibrosis. 27,28 Similar results were observed in a study with triple HIV, HCV, and HTLV-1 co-infection, in which HTLV-1-infected patients presented better outcomes for HCVassociated liver fibrosis. 26 The present study was performed to provide new insights into the interactions between HCV and HTLV-1 infections through an evaluation of abnormalities in hepatic parameters and the neurological outcomes of HCV/HTLV-1 co-infection.…”
Section: Introductionsupporting
confidence: 75%
“…The study groups displayed some similar characteristics to those of previous studies, such as a higher frequency of females among HTLV-1-infected patients, 3 and a predominance of males among HCV/HTLV-1 co-infected individuals. [26][27][28] Considering the infection routes, IDU was more frequent in the HCV/HTLV-1 co-infected group, as described previously. 36,37 It has been shown that IDU is a risk factor for coinfection involving HIV, HCV, and especially HTLV-2 in southern Brazil.…”
Section: Discussionmentioning
confidence: 77%
“…No particular risk factor could be identified for HTLV/HCV coinfected patients in Brazil. The use of intravenous drugs did not seem to be an important risk factor for these parenterally transmitted viruses; however, the use of unsafe injections for licit medicines in the past was likely responsible for most cases of HCV transmission in many parts of the country during the 1970s and 80s [Paraná et al, ; Cardoso et al, ; Milagres et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study among a group of the US thalassemia patients, 1·3 and 18·8% were anti‐HTLVAb and anti‐HCVAb positive, respectively, and 1 (0·45%) patient was found to be co‐infected with HCV/HTLV (Switzer et al , ). As HCV and HTLV‐1/2 can be transmitted by blood transfusion, the higher occurrence of co‐infection is expected in the populations at higher risk of blood‐borne viral infections (Milagres et al , ). In spite of HTLV‐associated illnesses that may occur in infected patients, the HTLV influences chronic hepatitis C outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences indicated that HTLV‐1 produces a functional impairment of cellular immune response. A study reported that the host and virus interaction can lead to cellular immune dysfunction in HCV/HTLV‐co‐infected patients, which might impair HCV clearance and lead to hepatitis C aggressive forms consequently (Milagres et al , ). As thalassemic patients need chronic blood transfusion that exposes them to different blood‐borne pathogens, HCV/HTLV co‐infection is prevalent among these patients, and as a result chronic hepatitis C should be treated promptly.…”
Section: Discussionmentioning
confidence: 99%